Seeing clearly without your lenses: digital holographic microscopy analysis of blood culture Gram stains - Mark D. Gonzalez (Journal of Clinical Microbiology, 2026)
ABSTRACT While automation and digital imaging technologies are now available for setup and workup of microbiology cultures, specimen Gram stain reading is still manually performed and requires experience to provide accurate results. In the article by K. P. Smith, E. Boulanger, M. Elkan, J. Fink, et al. (J Clin Microbiol 64:e01627-25, 2026, https://doi.org/10.1128/jcm.01627-25 ), the authors use a non-optical-based methodology, digital holographic microscopy, in combination with artificial intelligence to automate and provide interpretations and digital images of Gram stains from positive blood culture broths. While this differs from previous optical-based methods for Gram stain slide scanning, it demonstrated comparable performance. Gram stain slide staining and assistance by artificial intelligence for slide interpretation are a tantalizing future tool for clinical microbiology laboratories.